2016
DOI: 10.4102/safp.v58i3.5670
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mental health care services in primary health care clinics: a survey of primary health care nurses’ knowledge, attitudes and beliefs

Abstract: Background: Nurses are the main providers of care at primary health care (PHC) clinics; the high incidence of mental health problems at these clinics means that PHC nurses are important providers of mental health care. The PHC nurses’ knowledge regarding provision and identification of mental health problems has been shown to be poor. Aim: The study aimed to investigate the knowledge, attitudes and beliefs concerning the care of psychiatric patients at PHC level amongst nurses.Setting: The study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The nurses that register for a 4-year degree or diploma are taught psychiatric nursing, and when they complete their courses, they are placed either in the hospital or primary health care to care for the patients consulting in these settings. Furthermore, the literature review illustrated that to ensure that mental health conditions are appropriately identified and managed, primary health care clinics must have psychiatric-trained nurses on staff [15]. Furthermore, most nurses have a 4-year Diploma in Nursing, indicating that psychiatric nursing training is well represented in primary health care clinics [15].…”
Section: Skills and Training Of Nurses In Mental Health Care Manageme...mentioning
confidence: 99%
See 3 more Smart Citations
“…The nurses that register for a 4-year degree or diploma are taught psychiatric nursing, and when they complete their courses, they are placed either in the hospital or primary health care to care for the patients consulting in these settings. Furthermore, the literature review illustrated that to ensure that mental health conditions are appropriately identified and managed, primary health care clinics must have psychiatric-trained nurses on staff [15]. Furthermore, most nurses have a 4-year Diploma in Nursing, indicating that psychiatric nursing training is well represented in primary health care clinics [15].…”
Section: Skills and Training Of Nurses In Mental Health Care Manageme...mentioning
confidence: 99%
“…Furthermore, the literature review illustrated that to ensure that mental health conditions are appropriately identified and managed, primary health care clinics must have psychiatric-trained nurses on staff [15]. Furthermore, most nurses have a 4-year Diploma in Nursing, indicating that psychiatric nursing training is well represented in primary health care clinics [15]. Despite this, nurses with a 4-year diploma or degree do not have adequate skills and knowledge to manage patients presenting with mental health disorders in primary health care settings [15,38].…”
Section: Skills and Training Of Nurses In Mental Health Care Manageme...mentioning
confidence: 99%
See 2 more Smart Citations
“…Unfavorable working conditions, lack of resources, and demoralization of nurses have been reported to cultivate undesirable attitudes toward mental illness (Alburquerque‐Sendin et al, 2018 ). However, nurses in PHC should inform users and community members about mental health, identify mental disorders, and refer users to appropriate services (De Kock & Pillay, 2016 ), but unfortunately, most PHC nurses do not possess the knowledge, training, or experience to render care (Dube & Uys, 2016 ; Maconick et al., 2018 ). In addition, stigma and strong negative attitudes among PHC professionals have been found to challenge mental health support in the region (Kapungwe et al., 2011 ; Mosaku & Wallymahdmed, 2017 ).…”
Section: Introductionmentioning
confidence: 99%